CONSECUTIVE INTERPRETING STUDY IN PRESIDENT JOKO WIDODO AND BARACK OBAMA BILATERAL MEETING VIDEO - Lathifah Dinda Srijati; Yulia Sari Dewi Kusumawati Kusumawati; Ramadan Adianto Budiman (Acceleration: Multidisciplinary Research Journal, 2024)
This study examines consecutive interpreting strategies in the subject of a video bilateral meeting between Jokowi and Obama. This study examined a bilateral meeting in English and consecutively interpreted it in Indonesian. This study applied the consecutive interpreting strategy theory from (Faerch, & Kasper, 1983).  The descriptive qualitative method was used as the method of this study. Data were collected from videos taken from the website YouTube. After that, the video was transcribed conservatively. The result showed that two types of consecutive interpreting strategies were used. There are reduction and achievement strategies. From the reduction strategy, the interpreter used the skipping, incomplete sentence, and filtering techniques. Meanwhile, in the achievement strategy, the interpreter applied an elaborate technique. The message abandonment and assistance techniques were not found in this study. The result also showed that the interpreter regularly reduces and elaborates the lexical meaning of the word or phrase in the utterances. The interpreter elaborated on his understanding and added extra information in a way to make the sentences easy to understand by the audience.